Effects of galantamine and galantamine combined with nimodipine on cognitive speed and quality of life in mixed dementia: a 24-week, randomized, placebo-controlled exploratory trial (the REMIX study) - Paulo Caramelli; Jerson Laks; André Luis Fernandes Palmini; Ricardo Nitrini; Márcia Lorena Fagundes Chaves; Orestes Vicente Forlenza; Francisco de Assis Carvalho do Vale; Maira Tonidandel Barbosa; Cássio Machado de Campos Bottino; João Carlos Machado; Helenice Charchat-Fichman; Fabio Lorea Lawson (Arquivos de Neuro-Psiquiatria)
The effects of galantamine (GAL) on quality of life (QoL) and cognitive speed, as well its effects combined with nimodipine (NIM) in Alzheimer disease (AD) with cerebrovascular disease (mixed dementia), have not been explored. Method : Double-blind, placebo-controlled, multicenter Brazilian trial, studying the effects of GAL/NIM vs. GAL/placebo (PLA) in mild to moderate mixed dementia. Patients were randomized to receive GAL/NIM or GAL/PLA for 24 weeks. Primary efficacy measures were changes on a computerized neuropsychological battery (CNTB) and QoL Scale in Alzheimer's Disease (QoL-AD) from baseline to week 24. Results : Twenty-one patients received at least one drug dose (9 GAL/NIM and 12 GAL/PLA). Groups were matched for age, sex, education, cognitive and QoL scores at baseline. No significant differences were observed between groups on primary or secondary measures. QoL and cognitive performance showed significant improvement (p<0.05) from baseline when all GAL-treated patients were analyzed. Adverse events were predominantly mild to moderate. Conclusion : GAL treatment improved QoL in mixed dementia, in addition to its previously known cognitive benefits. The combination GAL/NIM was not advantageous. However, the small sample size precludes any definitive conclusions. Trial registered at ClinicalTrials.gov: NCT00814658